If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2y + 7) = 46 Reorder the terms: 2(7 + 2y) = 46 (7 * 2 + 2y * 2) = 46 (14 + 4y) = 46 Solving 14 + 4y = 46 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 4y = 46 + -14 Combine like terms: 14 + -14 = 0 0 + 4y = 46 + -14 4y = 46 + -14 Combine like terms: 46 + -14 = 32 4y = 32 Divide each side by '4'. y = 8 Simplifying y = 8
| 2x^2-66=6 | | 2s^2-7s+3=0 | | 49b^2-256=0 | | 3p+5q=-26 | | 3a-(9-7a)=34 | | (18-7n)+1=-9 | | 3x^2(x^2-7)-x^3(2x)=0 | | -7+4(1+8v)=35 | | -8(9k-7)=17 | | (-3x^3y/9y^2z)^-2 | | 8x+7+4x+43=180 | | 4(2x+6)-3=13x+21-5x | | 30=-5+16+3n | | -4=8-4w | | 5f-9+3=-35 | | 3x^2(x^2-7)=0 | | -81+3x=29-2x | | X=(40-2X) | | -8=3/8n | | -9(1+4d)=19 | | -12x-3y=-12 | | 55=4w-13 | | 3f-11=4 | | -8+9c=19 | | 1/4x=24-1/2x | | 8+9c=19 | | 4/5X1/3= | | -12x-12x^2=0 | | (Z+2)(9x-5)=0 | | 12x+y=-3 | | 2b^2+5b-63=0 | | 261=79-x |